2020
DOI: 10.1016/j.ajogmf.2020.100145
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of coronavirus disease 2019: severe acute respiratory syndrome coronavirus 2 RNA on the fetal side of the placenta in pregnancies with coronavirus disease 2019–positive mothers and neonates at birth

Abstract: Vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for coronavirus disease 2019 (COVID-19), is still a controversial issue and studies on transplacental transmission correlations are still limited. We report on our experience with placental SARS-CoV-2 markers of infection in a series of mothers who received a diagnosis of COVID-19 in their third trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
376
6
23

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(426 citation statements)
references
References 6 publications
21
376
6
23
Order By: Relevance
“…Defining the role of the GI tract in SARS-CoV-2 infection may also help understand the risks of vertical transmission during gestation since amniotic fluid is swallowed by the fetus during gestation and viral contamination has been isolated from the placenta of an affected woman 9 . While samples from affected mothers have so far failed to prove that amniotic fluid, cord blood, and breast milk contain SARS-CoV-2 10 , very limited data are available at this stage for pregnant women with COVID-19, and even fewer data are available on intrauterine vertical transmission 11 . While severe symptoms and death have been recorded in infants as young as 10 months of age 12 , very few cases of pathology in neonates have been associated with infection 13 and when 6 newborns from infected mothers were screened for SARS-CoV-2, they tested negative for the virus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Defining the role of the GI tract in SARS-CoV-2 infection may also help understand the risks of vertical transmission during gestation since amniotic fluid is swallowed by the fetus during gestation and viral contamination has been isolated from the placenta of an affected woman 9 . While samples from affected mothers have so far failed to prove that amniotic fluid, cord blood, and breast milk contain SARS-CoV-2 10 , very limited data are available at this stage for pregnant women with COVID-19, and even fewer data are available on intrauterine vertical transmission 11 . While severe symptoms and death have been recorded in infants as young as 10 months of age 12 , very few cases of pathology in neonates have been associated with infection 13 and when 6 newborns from infected mothers were screened for SARS-CoV-2, they tested negative for the virus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Of these 8, Patanè et al's study is the rst and only study we have identi ed which reports 2 cases of SARS-CoV-2 in the maternal, neonatal and placental tissue. Both of these mothers displayed signs and symptoms of SARS-CoV-2 [14]. Pen eld et al reported 3 positive placentas in women with severe to critical SARS-CoV-2 [13].…”
Section: Laboratory Investigationsmentioning
confidence: 95%
“…This literature review comprises 45 COVID-19 positive pregnant women whose placentas and neonates were also analysed by RT-PCR for the presence of SARS-CoV-2. We report no maternal mortality [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Maternal Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The current coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has raised, among many others, major concerns regarding the impact of infection during pregnancy. As of the time of this writing vertical SARS-COV-2 transmission remains controversial, while viral RNA has been detected in some placentas of COVID-19-affected mothers suggesting placental infection [1][2][3]. Emerging data on COVID-19-induced placental pathology are still limited [4,5].…”
Section: Introductionmentioning
confidence: 99%